Elite Figure Skaters Return to Sport Strategy Following Sports-Related Concussion: A Clinical Commentary - Brittani Freund; Gretchen Mohney (International Journal of Sports Physical Therapy)
# Background The Concussion in Sport Group (CISG) developed the 6th Consensus Statement on Concussion in Sport following the international conference held in Amsterdam in 2022. Their published statement provides recommendations and an updated Return to Sport (RTS) Strategy that can be adapted for different sports/disciplines. # Description Given the unique demands of figure skating—such as high-speed spins, jumps, inversions, and overhead lifts—this clinical commentary offers sport-specific guidance for healthcare practitioners (HCPs) managing elite figure skaters recovering from sports-related concussions (SRC). This adaptation focuses on reintroduction timing of vertical, rotational, and inversion elements. Further considerations regarding elite athletes and factors impacting recovery are also provided. While scientific evidence of SRCs continues to evolve, these recommendations were derived from the current and available research. # Clinical Relevance Given the complexity of figure skating and variability amongst multiple disciplines, the purpose of this clinical commentary is to provide recommendations and examples of how to apply the current RTS strategy to elite figure skaters following a SRC. # Level of Evidence 5